Palladium-based catalyst, its preparation method and application in hydrogen production from formic acid
Patent Information
- Application Number
- CN202410293876.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-14
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2044-03-14
AI Technical Summary
[0006]为了解决甲酸制氢催化剂催化活性低、产氢速率慢、制备工艺流程长、成本高的问题,本发明提供了一种高效的钯基催化剂及其制备方法,以及在甲酸制氢中的应用
[0022]金属氮化物(氮化钼、氮化钴)在甲酸制氢反应中具有一定的催化活性。本发明中将所制备的氮化钴氮化钼复合物作为载体,同时引入钯基催化剂作为活性中心。本发明发现,载体氮化钴氮化钼复合物与钯活性中心存在协同作用,有助于提升其甲酸制氢催化剂的反应活性和稳定性。
Abstract
Description
Technical Field
[0001] This invention belongs to the field of catalyst preparation technology, specifically relating to a palladium-based catalyst, its preparation method, and its application in the production of hydrogen from formic acid. Background Technology
[0002] Hydrogen energy, as a new type of clean energy, has received widespread attention in recent years. However, safe and efficient hydrogen storage and controlled hydrogen release have become key constraints on its large-scale application. The main problems currently facing hydrogen energy utilization include high storage and transportation costs, and high hydrogen production costs. One solution is chemical hydrogen storage methods, which use hydrogen-containing compounds to store hydrogen and utilize specific reactions and catalysts to produce hydrogen from the hydrogen elements inherent in the chemical substances themselves.
[0003] Formic acid (HCOOH, FA) is a common chemical raw material with high stability, non-toxicity, and high hydrogen density (4.4% hydrogen content). It can decompose to produce hydrogen at near-room temperature, making it an ideal hydrogen storage material and attracting considerable attention from researchers. Formic acid can be derived from renewable biomass or produced through H2 and CO2, playing a crucial role in accelerating the achievement of dual-carbon goals and building a clean, low-carbon, safe, and efficient energy system. Formic acid decomposition occurs via two pathways: dehydration (HCOOH → H2O + CO) and dehydrogenation (HCOOH → H2 + CO2). Currently, the main problems in formic acid-to-hydrogen production include low catalyst efficiency, high cost of precious metal catalysts, poor catalyst stability, and easy deactivation. Furthermore, the high concentration of CO in the byproducts can easily poison fuel cells. Therefore, designing and developing high-performance, low-cost catalysts is key to achieving large-scale application of formic acid-to-hydrogen production.
[0004] The study found that palladium (Pd)-based catalysts exhibit excellent catalytic activity in the formic acid decomposition for hydrogen production at near-room temperature. To further improve the hydrogen production performance of Pd-based catalysts, researchers have conducted numerous studies, mainly focusing on two aspects: (1) introducing second and third metal elements to construct alloy catalysts with the active center Pd. For example, gold (Au) (Applied Catalysis B: Environmental, 2021, 291, 120140) and silver (Ag) (Applied Surface Science, 2020, 512, 145746) are introduced to form bimetallic alloy catalysts with Pd. The introduction of the second element can effectively regulate the electronic structure of Pd, thereby improving its catalytic activity for formic acid hydrogen production; (2) screening and modification of the support. In recent years, researchers have reported on the use of graphene, molecular sieves, metal oxides, carbon nitride materials, and other materials to support the noble metal Pd for formic acid hydrogen production. For example, Zhao et al. functionalized a titanium dioxide-graphene composite support with amino groups and then loaded it with PdAg. The resulting PdAg metal alloy had an average particle size of 1.69 nm, and the catalyst achieved a TOF value of 1090 h⁻¹ for the dehydrogenation of formic acid at 25 °C. -1 (Journal of Energy Chemistry, 2021, 59: 455–464). Yu et al. encapsulated Pd particles of approximately 1.5 nm in the channels of a molecular sieve. This catalyst exhibited excellent catalytic activity in the dehydrogenation of formic acid, achieving a TOF value of 3027 h⁻¹ at 50 °C. -1 (J. Am. Chem. Soc. 2016,138:7484-7487).
[0005] However, although existing methods can effectively improve the catalytic performance of Pd-based catalysts in formic acid hydrogen production to some extent, they still suffer from problems such as low catalytic activity, slow hydrogen production rate, complex preparation processes of catalytic materials, and high cost. Therefore, developing highly efficient formic acid hydrogen production catalysts remains an urgent problem to be solved. Summary of the Invention
[0006] To address the problems of low catalytic activity, slow hydrogen production rate, long preparation process, and high cost in formic acid hydrogen production catalysts, this invention provides a highly efficient palladium-based catalyst, its preparation method, and its application in formic acid hydrogen production.
[0007] The technical solution of the present invention is as follows:
[0008] A method for preparing a palladium-based catalyst includes the following steps:
[0009] Step 1: Thoroughly mix water, molybdate, cobalt salt and nitrogen-containing compound, and perform hydrothermal reaction to obtain a complex of cobalt molybdate and nitrogen-containing compound;
[0010] Step 2: The cobalt molybdate complex with the nitrogen-containing compound is subjected to a pyrolysis reaction to obtain a cobalt nitride molybdenum nitride complex;
[0011] Step 3: The palladium precursor is loaded onto the cobalt nitride and molybdenum nitride composite and reduced to obtain the palladium-based catalyst.
[0012] Preferably, in step 1, the molar ratio of molybdenum atoms in the molybdate to cobalt atoms in the cobalt salt is 1:4-4:1.
[0013] Preferably, in step 1, the ratio of the sum of the masses of molybdate and cobalt salt to the mass of the nitrogen-containing compound is 1:2 to 1:6.
[0014] Preferably, in step 1, the molybdate is one or more of ammonium molybdate, sodium molybdate, or potassium molybdate; the cobalt salt is one or more of cobalt nitrate, cobalt chloride, or cobalt acetate; and the nitrogen-containing compound is one or two of melamine or dicyandiamide.
[0015] Preferably, the hydrothermal reaction in step 1 is carried out at a temperature of 150-200℃ for 4-24 hours.
[0016] Preferably, the temperature of the pyrolysis reaction in step 2 is 750-900℃ and the time is 0.5-4h.
[0017] Preferably, the reduction temperature in step 3 is 300-450℃ and the time is 1-4h.
[0018] Preferably, the palladium precursor in step 3 is one or more of chloropalladium, sodium tetrachloropalladium, or palladium acetate.
[0019] A palladium-based catalyst prepared by the method described above.
[0020] Application of a palladium-based catalyst prepared by the method described above in the production of hydrogen from formic acid.
[0021] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0022] Metal nitrides (molybdenum nitride, cobalt nitride) exhibit certain catalytic activity in the formic acid to hydrogen production reaction. In this invention, a prepared cobalt nitride-molybdenum nitride composite is used as a support, and a palladium-based catalyst is introduced as the active center. This invention reveals a synergistic effect between the supported cobalt nitride-molybdenum nitride composite and the palladium active center, which helps to improve the reactivity and stability of the formic acid to hydrogen production catalyst.
[0023] This invention employs hydrothermal and pyrolysis methods to prepare catalyst supports and impregnation methods to prepare target catalysts. The preparation process is simple, safe, and easy to operate. The prepared palladium-based formic acid hydrogen production catalyst exhibits good reactivity and hydrogen selectivity, which is of great significance for advancing the research and application of formic acid hydrogen production catalysts. Detailed Implementation
[0024] To facilitate understanding of the present invention, a more comprehensive description will be given below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a thorough and complete understanding of the disclosure of the present invention.
[0025] Example 1
[0026] 3.2 g of ammonium molybdate and 9.4 g of cobalt chloride (Mo / Co = 1 / 4) were dissolved in 50 g of deionized water. After complete dissolution, 25 g of melamine was added and stirred thoroughly. The resulting mixture was transferred to a sealed reactor and reacted at 160 °C for 6 h. The resulting product was centrifuged, dried, and ground into a powdered precursor. The powdered precursor was pyrolyzed in a high-temperature tube furnace at 750 °C and 50 mL / min under a nitrogen atmosphere for 2 h to obtain a molybdenum nitride and cobalt nitride composite. 1.9 mL of chloropalladium acid solution (concentration 0.05 mol / L) was dissolved in 10 mL of water, and 1 g of the molybdenum nitride and cobalt nitride composite was added. After ultrasonic vibration for 10 min, the mixture was transferred to a vacuum oven at 60 °C and dried for 10 h. Subsequently, the resulting product was reduced in a high-temperature tube furnace at 400 °C under a hydrogen atmosphere for 2 h to obtain the target catalyst.
[0027] The performance of formic acid to hydrogen production reaction was evaluated in a three-necked flask reactor using the water displacement method. Specifically, 10 mL of water was added to the three-necked flask, and the temperature was raised to 30 °C. Then, 0.2 g of catalyst was added. Subsequently, 10 mL of a 4 mol / L formic acid solution was added to the flask, and the cumulative water displacement was recorded at different reaction times. The time-to-flight (TOF) value was calculated using the hydrogen production volume in the first 20 minutes of the reaction. The test results showed that the TOF value of this catalyst was 422 h⁻¹ at a reaction temperature of 30 °C. -1 Gas chromatography was used to analyze the product gas, and no CO impurities were detected in the tail gas.
[0028] Example 2
[0029] 3.2 g of ammonium molybdate and 5.2 g of cobalt nitrate (Mo / Co = 1 / 1) were dissolved in 50 g of deionized water. After complete dissolution, 16.8 g of melamine was added and stirred thoroughly. The resulting mixture was transferred to a sealed reactor and reacted at 160 °C for 24 h. The resulting product was centrifuged, dried, and ground into a powdered precursor. The powdered precursor was pyrolyzed in a high-temperature tube furnace at 800 °C and 50 mL / min under a nitrogen atmosphere for 2 h to obtain a molybdenum nitride and cobalt nitride composite. 18.8 mL of chloropalladium acid solution (concentration 0.05 mol / L) was dissolved in 10 mL of water, and 1 g of the molybdenum nitride and cobalt nitride composite was added. After ultrasonic vibration for 10 min, the mixture was transferred to a vacuum oven at 60 °C and dried for 10 h. Subsequently, the resulting product was reduced in a high-temperature tube furnace at 400 °C under a hydrogen atmosphere for 2 h to obtain the target catalyst.
[0030] The performance of formic acid to hydrogen production reaction was evaluated in a three-necked flask reactor using the water displacement method. Specifically, 10 mL of water was added to the three-necked flask, and the temperature was raised to 50 °C. Then, 0.2 g of catalyst was added. Subsequently, 10 mL of a 4 mol / L formic acid solution was added to the flask, and the cumulative water displacement was recorded at different reaction times. The time-to-flight (TOF) value was calculated using the hydrogen production volume in the first 20 minutes of the reaction. The test results showed that the TOF value of this catalyst was 829 h⁻¹ at a reaction temperature of 50 °C. -1 Gas chromatography was used to analyze the product gas, and no CO impurities were detected in the tail gas.
[0031] Example 3
[0032] 2.5 g of sodium molybdate and 3.7 g of cobalt nitrate (Mo / Co = 4 / 1) were dissolved in 100 g of deionized water. After complete dissolution, 37.2 g of melamine was added and stirred thoroughly. The resulting mixture was transferred to a sealed reactor and reacted at 180 °C for 12 h. The resulting product was centrifuged, dried, and ground into a powdered precursor. The powdered precursor was pyrolyzed in a high-temperature tube furnace at 900 °C and 50 mL / min under a nitrogen atmosphere for 1 h to obtain a molybdenum nitride and cobalt nitride composite. 3.76 mL of chloropalladium acid solution (concentration 0.05 mol / L) was dissolved in 10 mL of water, and 1 g of the molybdenum nitride and cobalt nitride composite was added. After ultrasonic vibration for 10 min, the mixture was transferred to a vacuum oven at 60 °C and dried for 10 h. Subsequently, the resulting product was reduced in a high-temperature tube furnace at 350 °C under a hydrogen atmosphere for 1 h to obtain the target catalyst.
[0033] Example 4
[0034] 5.3 g of sodium molybdate and 3.7 g of cobalt nitrate (Mo / Co = 2 / 1) were dissolved in 50 g of deionized water. After complete dissolution, 27 g of dicyandiamide was added and stirred thoroughly. The resulting mixture was transferred to a sealed reactor and reacted at 150 °C for 24 h. The resulting product was centrifuged, dried, and ground into a powdered precursor. The powdered precursor was pyrolyzed in a high-temperature tube furnace at 800 °C and 50 mL / min under a nitrogen atmosphere for 2 h to obtain a molybdenum nitride and cobalt nitride complex. 2.82 mL of palladium acetate solution (concentration 0.1 mol / L) was dissolved in 10 mL of water, and 1 g of the molybdenum nitride and cobalt nitride complex was added. After ultrasonic vibration for 10 min, the mixture was transferred to a vacuum oven at 60 °C and dried for 10 h. Subsequently, the resulting product was reduced in a high-temperature tube furnace at 300 °C under a hydrogen atmosphere for 2 h to obtain the target catalyst.
[0035] The performance of formic acid to hydrogen production reaction was evaluated in a three-necked flask reactor using the water displacement method. Specifically, 10 mL of water was added to the three-necked flask, and the temperature was raised to 50 °C. Then, 0.2 g of catalyst was added. Subsequently, 10 mL of a 4 mol / L formic acid solution was added to the flask, and the cumulative water displacement was recorded at different reaction times. The time-to-flight (TOF) value was calculated using the hydrogen production volume in the first 20 minutes of the reaction. The test results showed that the TOF value of the catalyst was 851 h⁻¹ at a reaction temperature of 50 °C. -1 Gas chromatography was used to analyze the product gas, and no CO impurities were detected in the tail gas.
[0036] Example 5
[0037] 1.4 g of potassium molybdate and 5.8 g of cobalt acetate (Mo / Co = 1 / 4) were dissolved in 50 g of deionized water. After complete dissolution, 21.6 g of dicyandiamide was added and stirred thoroughly. The resulting mixture was transferred to a sealed reactor and reacted at 160 °C for 6 h. The resulting product was centrifuged, dried, and ground into a powdered precursor. The powdered precursor was pyrolyzed in a high-temperature tube furnace at 850 °C and 50 mL / min under a nitrogen atmosphere for 2 h to obtain a molybdenum nitride and cobalt nitride complex. 4.7 mL of palladium acetate solution (concentration 0.1 mol / L) was dissolved in 10 mL of water, and 1 g of the molybdenum nitride and cobalt nitride complex was added. After ultrasonic vibration for 10 min, the mixture was transferred to a vacuum oven at 60 °C and dried for 10 h. Subsequently, the resulting product was reduced in a high-temperature tube furnace at 400 °C under a hydrogen atmosphere for 4 h to obtain the target catalyst.
[0038] Example 6
[0039] 4.1 g of ammonium molybdate and 1.9 g of cobalt acetate (Mo / Co = 3 / 1) were dissolved in 50 g of deionized water. After complete dissolution, 30 g of dicyandiamide was added and stirred thoroughly. The resulting mixture was transferred to a sealed reactor and reacted at 160 °C for 6 h. The resulting product was centrifuged, dried, and ground into a powdered precursor. The powdered precursor was pyrolyzed in a high-temperature tube furnace at 750 °C and 50 mL / min under a nitrogen atmosphere for 2 h to obtain a molybdenum nitride and cobalt nitride complex. 3.76 mL of sodium tetrachloropalladium solution (concentration 0.1 mol / L) was dissolved in 10 mL of water, and 1 g of the molybdenum nitride and cobalt nitride complex was added. After ultrasonic vibration for 10 min, the mixture was transferred to a vacuum oven at 60 °C and dried for 10 h. Subsequently, the resulting product was reduced in a high-temperature tube furnace at 400 °C under a hydrogen atmosphere for 4 h to obtain the target catalyst.
[0040] The performance of formic acid to hydrogen production reaction was evaluated in a three-necked flask reactor using the water displacement method. Specifically, 10 mL of water was added to the three-necked flask, and the temperature was raised to 50 °C. Then, 0.2 g of catalyst was added. Subsequently, 10 mL of a 4 mol / L formic acid solution was added to the flask, and the cumulative water displacement was recorded at different reaction times. The time-to-flight (TOF) value was calculated using the hydrogen production volume in the first 20 minutes of the reaction. The test results showed that the TOF value of the catalyst was 578 h⁻¹ at a reaction temperature of 50 °C. -1 Gas chromatography was used to analyze the product gas, and no CO impurities were detected in the tail gas.
Claims
1. A method for preparing a palladium-based catalyst, characterized in that: Includes the following steps: Step 1: Water, molybdate, cobalt salt and nitrogen-containing compound are thoroughly mixed and subjected to hydrothermal reaction to obtain a complex of cobalt molybdate and nitrogen-containing compound; the nitrogen-containing compound is one or both of melamine or dicyandiamide; the hydrothermal reaction temperature is 150-200 ℃ and the time is 4-24 h; Step 2: The cobalt molybdate complex with the nitrogen-containing compound is subjected to a pyrolysis reaction to obtain a cobalt nitride molybdenum nitride complex; Step 3: The palladium precursor is loaded onto the cobalt nitride and molybdenum nitride composite and reduced to obtain the palladium-based catalyst.
2. The method for preparing the palladium-based catalyst according to claim 1, characterized in that: In step 1, the molar ratio of molybdenum atoms in the molybdate to cobalt atoms in the cobalt salt is 1:4-4:
1.
3. The method for preparing the palladium-based catalyst according to claim 1, characterized in that: In step 1, the ratio of the sum of the masses of molybdate and cobalt salt to the mass of the nitrogen-containing compound is 1:2 to 1:
6.
4. The method for preparing the palladium-based catalyst according to claim 1, characterized in that: In step 1, the molybdate is one or more of ammonium molybdate, sodium molybdate, or potassium molybdate; the cobalt salt is one or more of cobalt nitrate, cobalt chloride, or cobalt acetate.
5. The method for preparing the palladium-based catalyst according to claim 1, characterized in that: In step 2, the pyrolysis reaction is carried out at a temperature of 750-900 ℃ for a time of 0.5-4 h.
6. The method for preparing the palladium-based catalyst according to claim 1, characterized in that: The reduction temperature in step 3 is 300-450 ℃, and the time is 1-4 h.
7. The method for preparing the palladium-based catalyst according to claim 1, characterized in that: In step 3, the palladium precursor is one or more of chloropalladium, sodium tetrachloropalladium, or palladium acetate.
8. A palladium-based catalyst prepared by the preparation method according to any one of claims 1 to 7.
9. The application of a palladium-based catalyst prepared by any one of claims 1 to 7 in the production of hydrogen from formic acid.
Citation Information
Patent Citations
Nitride supported palladium catalyst and preparation method and application thereof
CN114100653A
Co-mo bimetallic nitride catalysts and preparation thereof
KR100238458B1